2019
DOI: 10.3389/fphar.2018.01452
|View full text |Cite
|
Sign up to set email alerts
|

CGRP Is Critical for Hot Flushes in Ovariectomized Mice

Abstract: Hot flushes are common and troublesome symptoms of menopause. The neuropeptide calcitonin gene-related peptide (CGRP) is increased in plasma during hot flushes but it has not been clear if CGRP is causally involved in the mechanism underpinning the flushes. Here, we examined the effect of interventions with CGRP in a mouse model of hot flushes based on flush-like temperature increases triggered by forced physical activity in ovariectomized mice. Compared to normal mice, ovariectomized mice reacted with an exag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Since αCGRP was lost also during development in these mice, other compensatory mechanisms might have been activated. However, we have previously shown that the mouse line used have deficits in an animal model for hot flushes 28 . This shows that there is no full and general compensation for the lack of αCGRP in this mouse line, but a lack of compensation regarding one readout does not exclude compensation in another response.…”
Section: Discussionmentioning
confidence: 99%
“…Since αCGRP was lost also during development in these mice, other compensatory mechanisms might have been activated. However, we have previously shown that the mouse line used have deficits in an animal model for hot flushes 28 . This shows that there is no full and general compensation for the lack of αCGRP in this mouse line, but a lack of compensation regarding one readout does not exclude compensation in another response.…”
Section: Discussionmentioning
confidence: 99%
“…A study in mice showed that blocking CGRP reduced flush-like symptoms [26], suggesting that anti-CGRP treatment, antagonists or antibodies, could potentially diminish perimenopausal vasomotor symptoms by stabilizing the CGRP fluctuations. Several studies on the effect of hormonal replacement therapy on CGRP levels have reported that after 3 months of treatment, the plasma concentration of CGRP in postmenopausal women significantly increases to levels similar to healthy fertile women [27,28], suggesting a reduced CGRP secretion after menopause, probably associated to sex hormone deficiency [27].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Since the mouse line used has been shown to have deficits in CGRP-dependent responses including hot flushes 27 it is unlikely that compensatory mechanisms can explain the lack of effect in our studies.…”
Section: Discussionmentioning
confidence: 89%